PERLINDUNGAN HUKUM TERHADAP DEBITUR ATAS PERMOHONAN PAILIT YANG DIAJUKAN OLEH KREDITUR TIDAK BERITIKAD BAIK - Syarifah Rohmatulloh; Putu Eka Trisna Dewi; Karyoto (Jurnal Hukum Saraswati, 2024)
Protection of debtors is very important, in order to guarantee certainty, justice and legal benefits in society. Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. This regulation was issued in order to provide certainty, justice and legal benefits as well as fulfill business interests in resolving all issues related to the company's debts. Apart from that, this regulates the protection of the rights of the parties in the subject of bankruptcy. However, sometimes existing regulations are not implemented properly so that the effectiveness of existing regulations does not apply optimally. So maximum efforts are needed to achieve a desired legal goal. In this research the author uses normative juridical research methods by examining the extent to which Law Number 37 of 2004 can overcome problems related to debtors in bankruptcy. The insolvency test is a form of legal protection for debtors who still have good solvency and have good intentions.